Impact of religious participation, social interactions and globalisation on meat consumption: Evidence from India - Massimo Filippini; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
From both health and environmental policy perspectives, it is advisable to ensure that individuals maximise the nutritional gains from eating meat, without having a significantly adverse environmental impact, i.e. sustainable meat consumption pathways are imperative. This is especially true for developing countries, where rising incomes and growing populations have meant that meat consumption has also risen. India is an example of a country where a large share of the population has been vegetarian due to religious and cultural factors, although this is rapidly changing. In this paper, we hypothesise that social interactions and globalisation are two factors that explain this shift in consumption behaviour, especially amongst Hindu households. These hypotheses are based on the theoretical findings of Levy and Razin (2012). The empirical results show that Hindus that are members of religious groups are less likely to eat meat than non-member Hindus, whereas Hindus that are members of non-religious types of groups are more likely to eat meat than non-members. We also find that Hindu households that frequently use sources of media such as newspapers, the radio or television are more likely to consume meat compared to Hindus that do not. This paper provides important policy implications, both in terms of the formulation of Nationally Recommended Diets in developing countries, and in terms of identifying the channel of influence of both social networks and globalisation on social and religious norms, consumption behaviour, and ultimately, on climate change.
Keywords: D83; Q18; Q54; C23; C26; 330; Meat consumption; Religious norms; Social interactions; Globalisation; India